[PP.01.24] THE ANTIHYPERTENSIVE THERAPY EFFICIENCY AMONG OUTPATIENTS IN MOSCOW. (September 2017) - Ostapenko, V.; Tkacheva, O.; Runikhina, N.; Kotovskaya, Y.; Sharashkina, N.
Abstract : Objective: The purpose of the study is to evaluate the antihypertensive therapy efficiency within outpatients > 65 years old in Moscow. Design and method: The study includes 356 patients 65–93 years old. Average age was 74.8 ± 6.1 y.o., 80.4% women, 54.8% of them with higher education and 9% still continue to work. Research conducted in Moscow polyclinic from November 2014 to May 2015. Anamnesis of arterial hypertension, cardiovascular diseases and antihypertensive therapy was evaluated among 2 groups of the seniors: 65–79 y.o. (n = 277) and > 80 y.o. (n = 79). The measurement of blood pressure (BP) was made in sitting position using validated device. Results: Based on patients self-report prevalence of arterial hypertension was 88.5% (n = 315). It was insignificantly higher among patients > 80 y.o. (91.1%) than in group of 65–79 y.o. (87.7%). Around 92% of the patients took antihypertensive therapy. Average BP level was 145.5 ± 24.1 / 78.8 ± 11.5 mm Hg. Systolic BP (SBP) without hypertension was 135.2 ± 17.5 mmHg. In group of treated hypertensive patients SBP was 145.8 ± 28.1 mmHg. In the group of untreated patients - 154.3 ± 26 mmHg, respectively. SBP > 140 mm Hg was observed in 51.1%, diastolic BP > 90 mm Hg in 11.8% among all patients. In 38.6% treated subjects SBP was < 140 mmHg, in 34.7% - > 150 mmHg. The age has significant impact on diastolic BP level. Average BP level among 65–79 y.o. patients reveal 145, 5 ± 26, 7 / 79, 8 ± 14 mmHg. However the results of BP level among > 80 y.o. was 145, 5 ± 25, 3/ 75, 2 ± 11, 5. Conclusions: Study describes high prevalence of hypertension and lack of efficiency antihypertensive therapy within the outpatients > 65 years in Moscow.